(untitled) (Journal of Science and Technology, 2016)
A cross-sectional survey was conducted in the Ejisu-Juaben District to determine the prevalence of asymptomatic malaria and anaemia, and treatment outcomes in pupils of seven public schools public schools in a rural community in the forest belt of Ghana. Children with confirmed malaria parasites were randomly assigned to be treated with Artemisinin-based combination therapies available on the Ghanaian market. Post-treatment days 14 and 28 follow-up blood samples were taken to determine the treatment outcomes on peripheral parasitaemia and haemoglobin (Hb) concentrations. Out of 812 pupils (without malaria symptoms) who were screened, the baseline parasitaemia prevalence was 58.6%. Parasitaemia prevalence across the seven (7) public schools ranged from 49.7% to 71.0% (p =0.002). Post-treatment parasitaemia among the different treatment regimes were significant only at day 28 (p<0.001). The mean Hb concentration on the screening day was 10.5g/dl and over 60% of pupils were mildly anaemic (Hb <11.0g/dl) whereas 14% had Hb <8.0g/dl. Post-treatment Hb concentrations of pupils by days 14 and 28 were 11.4g/dl and 11.7g/dl with an improvement of 0.7g/dl and 0.9g/dl respectively over the baseline Hb concentration (p<0.001). The overall proportion of children with Hb concentrations <11.0g/dl was 32.6% and 25.3% by days 14 and 28 respectively. The burden of malaria and anaemia among school children is high and warrants investment to reduce these levels. These findings could be a reflection of the health situation that pertains in the basic public schools especially in the rural forest areas of Ghana.